Agaricus bisporus and its by-products as a source of valuable extracts and bioactive compounds. (15th September 2019) - Ramos, Marina; Burgos, Nuria; Barnard, Almero; Evans, Gareth; Preece, James; Graz, Michael; Ruthes, Andrea Caroline; Jiménez-Quero, Amparo; Martínez-Abad, Antonio; Vilaplana, Francisco; Ngoc, Long Pham; Brouwer, Abraham; et al.
Abstract: Edible mushrooms constitute an appreciated nutritional source for humans due to their low caloric intake and their high content in carbohydrates, proteins, dietary fibre, phenolic compounds, polyunsaturated fatty acids, vitamins and minerals. It has been also demonstrated that mushrooms have health-promoting benefits. Cultivation of mushrooms, especially of the most common species Agaricus bisporus, represents an increasingly important food industry in Europe, but with a direct consequence in the increasing amount of by-products from their industrial production. This review focuses on collecting and critically investigating the current data on the bioactive properties of Agaricus bisporus as well as the recent research for the extraction of valuable functional molecules from this species and its by-products obtained after industrial processing. The state of the art regarding the antimicrobial, antioxidant, anti-allergenic and dietary compounds will be discussed for novel applications such as nutraceuticals, additives for food or cleaning products.